The graduation of Jake Moon - Park, Barbara (New York : Scholastic, 2000)
Fourteen-year-old Jake recalls how he has spent the last four years of his life watching his grandfather descend slowly but surely into the horrors of Alzheimer's disease.
Keywords: Illness -- Family; Chapter book -- Funny